Business Model Innovation for Additive Manufacturing Technology: A Literature Review - Naser, Bushra (2020)
Purpose: The aim of this research is to capture the essence of the business model within the additive manufacturing context in academic literature. Also, it aims to identify the contexts and underlying themes in which the business model is being discussed in the literature. Furthermore, the research aims to highlight articles that contributed to the body of knowledge and was widely cited in the literature. Finally, the research aim is to address the gaps identified in the literature by proposing open research questions that need to be addressed in the future. Methodology: The methodology adopted for this research is a systematic literature review (SLR). Based on secondary data from journal articles and a qualitative approach, this research method seeks to analyze the scattered literature related to business models for additive manufacturing and combine and summarize all relevant articles for this field in one research. Findings: The main findings from the SLR are: • Identifying main contexts and underlying themes The main contexts identified in the literature are user involvement, platforms and open source communities, ecosystem and business model innovation, innovation lessons and future scenarios, supply chain, production and manufacturing, and other-contexts. Other-contexts category grouped articles from topics that are least discussed in the literature such as circular economy and democratization. The main underlying themes observed in these contexts are innovation and operations. • Identifying significant contributions to the body of knowledge • Proposing open research questions for future researches Research limitations/ implications: Open research questions were proposed to address gaps identified after reviewing the literature. Further research should try to answer these questions scientifically to reach a better understanding of this area of research. Originality/ value: This research builds an including/excluding criteria model based on four pillars; that can be used in future research to analyze business models in different fields of study. In addition, the value of this research lies in the fact that it significantly contribute in terms of understanding business models for additive manufacturing by proposing a comprehensive framework; which provides the foundation for further work in this area. Key words: Additive manufacturing technology, business model.